IMPLEMENTATION OF FINANCING MANAGEMENT IN THE MAINTENANCE OF FACILITIES AND INFRASTRUCTURE AT MUHAMMADIYAH 1 CANDI LABSCHOOL UMSIDA - Aprilianti, Irda; Andriani, Nurdiana Faizah; Rahmawati, Imelda (Journal of Learning on History and Social Sciences, 2024)
This The purpose of this study is to see and understand how school financial management affects the fulfillment of educational infrastructure facilities at SD Muhammadiyah 1 Candi. This study used a qualitative case study method. The leader, secretary, and treasurer are the informants of this study. The data were collected through interviews, participant observation, and documentation. The data analysis used reduction, display, and drawing/verifying conclusions. Credibility, transferability, dependability, and confirmability were the metrics used to ensure the validity of the data. According to the results of the study, school financial management to provide educational facilities for SD Muhammadiyah 1 Candi is carried out through budget planning (budgeting), budget absorption, bookkeeping (accounting), and accountability (accountability). This research shows that financial management is very important to provide educational facilities and infrastructure by involving stakeholders